A new measurement system for performance analysis in flatwater sprint kayaking - Bonaiuto, V.; Gatta, G.; Romagnoli, C.; Boatto, P.; Lanotte, N.; Annino, G. (Proceedings, 2020)
The full comprehension of the impact with which each force is involved in kayak propulsion is very difficult. The measure of the force on the paddle or the stroke rate only is often not enough for the coach to identify the best actions useful to improve the performances of a kayaker. To this purpose, the synchronous measurement of all parameters involved in the kayak propulsion, both dynamic (force acting on paddle and foot brace) and kinematic (stroke frequency, displacement, velocity, acceleration, roll, yaw, and pitch of the boat) could suggest to the coach more appropriate strategies for better understanding of the paddler`s motion and the relevant effects on the kayak behavior. Some simulation models, as well as measurement systems of increasing complexity, have been proposed in the recent years. In this paper, we present the e-Kayak system: A multichannel Digital Acquisition (DAQ) system specifically customized for flatwater kayaking. The system will be described in depth and its capability investigated through specific measurement results.